Pet Plastic Bottle Waste with Reuse Approach as Interior Pre-Fabrication Modules for Interior Wall - Ignatius Adrian Santana; Dalhar Susanto; Widyarko Widyarko (Universitas Lampung, 2017)
Abstract—PET plastic bottle is one of the main source of waste in big cities. This research aims to find out the possibility of reusing PET bottle as pre fabrication wall module material. The pre fabrication concept were offered so that in the construction phase, the instalation of this material will be fast, efficient, and able to minimalize the waste potential. The method to decided the PET bottle specimen was by surveying some sample location in Jakarta to found out the type and capacity of PET bottle waste. Bottle waste that has the highest volume, was selected to be the speciment for further experiment as pre fabrication modul. To determine the strength capacity of this material, some module variation were designed for compressive and flexural strength test. This research is a preliminary experiment to understanding the basic potential of PET bottle as building material. This research expected to support the use of PET bottle waste for other uses in building constructionKeywords— reuse, PET bottle, pre-fabrication, module.